Incidence of Breast Cancer in Phitsanulok Province - Wongtala, Prathan (Asian Health, Science and Technology Reports, 2007)
This research was carried out to identify the incidence of breast cancer in Phitsanulok from January 1 to December 31, 2005. All twenty hospitals in nine districts of Phitsanulok were included for data collection of breast cancer patients. The ICD-9 program identified 202 patients with breast cancer who lived in Phitsanulok and were included in the analysis. The result of the study revealed that the incidence rate of breast cancer per 100,000 in the year 2005 was 29.75. When gender was considered, the incidence rate of breast cancer per 100,000 was 1.47 for males and 57.30 for females. The age-standardized incidence rate (ASR) of breast cancer in Phitsanulok was 24.50: 1.77 among men and 23.67 among women. Using holistic considerations, a high rate of ASR was shown in Bang Kratum, Phrom Phiram and Wat Bot Districts being 118.71, 44.75 and 42.22, respectively. Additionally, Noen Maprang District had the lowest ASR at 8.12. When compared to the highest ASR in Thailand, the ASR per 100,000 in Phitsanulok was less than that in the Pra Khanong District of Bangkok (81.1 in the year 2001). In conclusion, this study have identified the incidence of breast cancer in Phitsanulok. The ASR of this report provides useful evidence for evaluation and monitoring of breast cancer in Phitsanulok.